Business ethics as an object of scientific research - K.Ye.; S.Yu. (Економіка, управління та адміністрування)
The growing complexity of the functioning conditions of domestic business entities places special emphasis on issues related to ensuring that not only economic, but also environmental and social aspects of the enterprise are taken into account. With this in mind, the article is devoted to the definition of “business ethics” concept and its characteristic features in the context of scientific research in managerial sciences. It has been established that the difficulty of identifying the concept of “business ethics” is conditioned by the lack of legal interpretation of this term, as well as by the presence of related concepts (corporate social responsibility, corporate ethics, managerial ethics, etc.). It has been found that business ethics and corporate social responsibility are interdependent and interrelated concepts, while the categories of “corporate ethics” and “managerial ethics” are subordinate to business ethics. Based on the study of foreign and domestic scientific publications, the authors’ approach to the interpretation of the studied category has been formulated. It is proposed to understand business ethics as a system of values, norms, and rules of behavior that regulate relations in the internal environment of the enterprise, as well as communication with external stakeholders and serve as a tool for implementing the concept of corporate social responsibility. The article defines that business ethics covers a wide range of relations, both internal (between employees of the business entity) and external (between the business entity and external stakeholders). The characteristics of the key spheres of relations that are the subject of business ethics has been substantiated. It has been determined that the formation of business ethics on the basis of efficiency and rationality involves compliance with relevant principles, the key of which are the following: honesty, decency, professionalism, responsibility, mutual respect and tolerance, harmony and balance.